Transvenous Embolization of a Direct Carotid Cavernous Fistula through the Pterygoid Plexus - Chun, Galen F.H.; Tomsick, Thomas A. (American Journal of Neuroradiology, 2002)
Summary: Closure of a direct carotid cavernous fistula with detachable coils by transpterygoid venous approach to the cavernous sinus is an alternative technique that may be applied in cases in which other techniques offer increased risk or in which other techniques have failed. In this case report, we present the details of the management of a direct carotid cavernous fistula by this method.